Large-scale clustering in bubble models - Amendola, Luca; Borgani, Stefano (Arxiv, 1993)
We analyze the statistical properties of bubble models for the large-scale distribution of galaxies. To this aim, we realize static simulations, in which galaxies are mostly randomly arranged in the regions surrounding bubbles. As a first test, we realize simulations of the Lick map, by suitably projecting the three-dimensional simulations. In this way, we are able to safely compare the angular correlation function implied by a bubbly geometry to that of the APM sample. We find that several bubble models provide an adequate amount of large-scale correlation, which nicely fits that of APM galaxies. Further, we apply the statistics of the count-in-cell moments to the three-dimensional distribution and compare them with available observational data on variance, skewness and kurtosis. Based on our purely geometrical constructions, we find that a well defined hierarchical scaling of higher order moments up to scales $\sim 70\hm$. The overall emerging picture is that the bubbly geometry is well suited to reproduce several aspects of large-scale clustering.